THE CONCEPT AND IMPLEMENTATION OF SUSTAINABILITY ACCOUNTING IN THE CIRCULAR ECONOMY OF WASTE MANAGEMENT (CASE STUDY: BONTANG CITY WASTE BANK) - Sitti Rahma Sudirman; Mega Norsita; Abd Rahman Maulana (Jurnal Penelitian Progresif, 2026)
This study analyzes the implementation of sustainability accounting in the circular economy of waste management at the Bontang City Waste Bank. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and document analysis. The findings reveal an uneven implementation of the Triple Bottom Line (TBL). While the economic aspect is well-structured with financial records, the social and environmental impacts remain undocumented. Key barriers are limited human resource capacity and a minimalistic accounting system. This study contributes empirically to sustainability accounting literature in community-based circular economy initiatives and recommends simple TBL based reporting templates and training.